2023
DOI: 10.5430/wjel.v13n5p200
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Power of Hedges: Insights from TED Talks

Abstract: The corpus-based study focuses on the use of hedges in persuasive TED Talk speeches, which are powerful, premeditated speeches delivered in a distinctive communicative environment that combines elements of both spoken and written discourse. The authors employ both quantitative and qualitative methods to analyze the hedging devices used to bolster the three rhetorical appeals: ethos, pathos, and logos. The results show that only 2% of the words in the corpus serve as hedging devices, which is lower compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Many studies investigated Hedges and Boosters related to speech (Jovic et al, 2023), (Azlia, 2022), and(Vebriyanto et al, 2019) on contrary research on hedges and booster deals with talk are limited to be found. With Hyland's theory, the researcher has an interest in studying more deeply related to Hedges and Boosters.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigated Hedges and Boosters related to speech (Jovic et al, 2023), (Azlia, 2022), and(Vebriyanto et al, 2019) on contrary research on hedges and booster deals with talk are limited to be found. With Hyland's theory, the researcher has an interest in studying more deeply related to Hedges and Boosters.…”
Section: Introductionmentioning
confidence: 99%